Effects of music-based intervention on english proficiency among primary school pupils in Selangor, Malaysia - Lum, Li Yuen (2021)
Based on existing research, the current status of English literacy skills among low performing pupils in national primary schools is a serious cause for concern. Primary students in Malaysia are still struggling to acquire strong foundation of speaking skill in the target language. Early intervention to tackle this problem is critical to help children catch up with the expected educational standards which includes speaking, listening, reading, and writing skills at each level of study. However, teacher faced challenges in creating the environment for teaching and learning English to meet current needs. The issues identified in the region's implementation of the CEFR revealed several nearly indistinguishable issues, including teachers' extremely limited knowledge and exposure to the CEFR, a shortage of local CEFR experts capable of producing local CEFR textbooks, a lack of adequate training, and the perception that many teachers struggled to incorporate the CEFR into their daily teaching (Foley, 2019: Ngu & Aziz 2019). Therefore, this study set out to investigate the effects of music-based intervention on English proficiency among primary school pupils by using improvised teaching materials form the CEFR Year 3 syllabus as material ought to be able to satisfy students’ require and, both present and future needs and to examine the participation level of pupils from the music-based intervention. This research employed a quantitative approach with a pre-test-post-test quasi-experimental design. A total of forty Year Three Students (N = 40 pupils, divided into 2 groups; experimental and control group) participated in the study. Data was collected using speaking assessments and observation checklist. The findings of the study showed that there was a significant difference between the quasi-experimental groups following music-based intervention with improvised materials and control group using the conventional learning with materials provided by Ministry of Education (MOE). On top of that, students who had gone the through music-based intervention using improvised materials had showed improvement not only in the content and vocabulary in the materials, but also their speaking skills, especially their pronunciation and fluency. Results also illustrated that the inclusion of a music-based Intervention and improvised materials in English class appears to have motivated the pupils to participate actively in the class discussion. In summary, the results demonstrate that the music-based intervention helped in enhancing English proficiency among the primary pupils.